Apolipoprotein E gene polymorphism modifies fasting total cholesterol concentrations in response to replacement of dietary saturated with monounsaturated fatty acids in adults at moderate cardiovascular disease risk. Issue 1 (December 2017) - Shatwan, Israa; Weech, Michelle; Jackson, Kim; Lovegrove, Julie; Vimaleswaran, Karani
Abstract Background Consumption of ≤10% total energy from fat as saturated fatty acids (SFA) is recommended for cardiovascular disease risk reduction in the UK; however there is no clear guidance on the optimum replacement nutrient. Lipid-associated single-nucleotide polymorphisms (SNPs) have been shown to modify the lipid responses to dietary fat interventions. Hence, we performed a retrospective analysis in 120 participants from the Dietary Intervention and VAScular function (DIVAS) study to investigate whether lipoprotein lipase (LPL ) and apolipoprotein E (APOE ) SNPs modify the fasting lipid response to replacement of SFA with monounsaturated (MUFA) or n-6 polyunsaturated (PUFA) fatty acids. Methods The DIVAS study was a randomized, single-blinded, parallel dietary intervention study performed in adults with a moderate cardiovascular risk who received one of three isoenergetic diets rich in SFA, MUFA or n-6 PUFA for 16 weeks. Results After the 16-week intervention, a significant diet-gene interaction was observed for changes in fasting total cholesterol (P = 0.001). For theAPOE SNP rs1064725, only TT homozygotes showed a significant reduction in total cholesterol after the MUFA diet (n = 33; −0.71 ± 1.88 mmol/l) compared to the SFA (n = 38; 0.34 ± 0.55 mmol/l) or n-6 PUFA diets (n = 37; −0.08 ± 0.73 mmol/l) (P = 0.004). None of the interactions were statistically significant for the other SNPs. Conclusions In summary, our findings have demonstrated a greater sensitivity of theAPOE SNP rs1064725 to dietary fat composition, with a total cholesterol lowering effect observed following substitution of SFA with MUFA but not n-6 PUFA. Further large intervention studies incorporating prospective genotyping are required to confirm or refute our findings. Trial registration The trial was registered atwww.clinicaltrials.gov as NCT01478958.